Assessing the combining role of public-private investment as a green finance and renewable energy in carbon neutrality target. (August 2022) - Lu, Qingchang; Farooq, Muhammad Umar; Ma, Xiaoyu; Iram, Robina
Abstract: All governments have lately placed a high priority on achieving carbon neutrality. Environmental sustainability may be achieved via the evaluation of novel approaches. We are looking at the impact of China's public-private energy and efficiency partnerships on the country's carbon dioxide emissions from 1990Q1 to 2019Q4. Furthermore, we include sustainability initiatives, sustainable sources, green finance, and financial progress into our model to better understand carbon dioxide emissions. Econometric regression techniques, such as dynamic ordinary least squares (DOLS) and FMOLS, are used in this work. The research also showed that financial inclusion positively impacts the goal of green finance attainment. According to the findings, China's economic growth and public-private collaboration positively impact carbon emissions. Emissions of carbon dioxide gases, on the other hand, are negatively influenced by improvements in energy efficiency, renewable energy, and technical innovation. Public-private partnerships in energy production must be more efficient to reduce carbon emissions. Chinese policymakers must guarantee a successful and prompt changeover to renewable energy sources via environmental, technological adaptation, and efficient use of all renewable resources. Highlights: There is a dire need to measure the relationship between Energy Productivity and Public-private Investment. The effects of Energy Productivity and Public-private Investment on Carbon dioxide emission has been measured. Dynamic Ordinary Least Squares (DOLS) and FMOLS was conducted to examine the Impact. China's economic growth and public-private collaboration have a positive impact on carbon emissions. In order to reduce carbon emissions, public-private partnerships in energy production must be made more efficient.